RISK AND ADVENTURE SPORTS IN THE MOUNTAINS: A PATH ALONG A GAME WITH LIMITS AND UNCERTAINTIES (Fiep Bulletin - online, 2012)
This text aims at clarifying the meanings of adventure and risk expressed in publicity sites related to tourism involving adventure sports, and in the discourse of nature sports practitioners, evidencing the symbolic and mythical elements that emerge from that discourse.
Keywords: adventure; risk; nature sports; social imaginary.